How To Choose The Appropriate Physical Activity For A Child With Autism Spectrum Disorder - mounira, Beggar (Journal of Sport Science Technology and Physical Activities, 2025)
"This theoretical study aimed to provide insights into how to select the most suitable physical activity for children with Autism Spectrum Disorder (ASD). The study concluded that identifying the specific type of autism the child is affected by is crucial in guiding the selection of the appropriate physical activity, which helps in managing or reducing the disorders characteristic of children with autism. Additionally, diagnosis is an essential element that cannot be overlooked in this process. In this regard, the study explored the different types of autism and the sports suitable for each type, based on the characteristics associated with the level of disturbance in individuals with ASD, while also identifying the appropriate physical activities for each stage. The study also clarified the methods and stages of diagnosing autism cases, relying on the criteria of the fifth edition of the Diagnostic and Statistical Manual of Mental Disorders (DSM-5), and highlighted the necessary medical specialties required for diagnosis."